Surface ruptures of the Mw 6.8 March 2011 Tarlay earthquake, Eastern Myanmar - Tun, Soe Thura (2014)
Field observations indicate the Mw 6.8 Tarlay, Myanmar, earthquake of 24 March 2011 resulted from the rupture of a short section of the left‐lateral Nam Ma fault. We document coseismic left‐lateral offsets that range from approximately 10 cm to about 2 m along a 19 km long section of the fault, based upon both field investigations and the interpretation of high‐resolution satellite imagery. Comparison of these early field and later remote measurements suggests that most of the paddy‐field offsets became obscured within a year or two. Our measurements indicate the magnitude of sinistral offset decreases gradually eastward from the epicentral area to the rupture terminus within the Tarlay basin, along the southern edge of a 2–3 km wide transtensional stepover.